2014
DOI: 10.5322/jesi.2014.23.7.1253
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Hazardous Chemicals for Effluents of STPs and WWTP in the Nakdong River Basin

Abstract: This study was investigated twenty two hazardous chemicals compounds for effluents of nine sewage treatment plants (STPs) and one waste water treatment plant (WWTP) in the Nakdong Ri-ver Basin. They are eleven phthalates(DMP, DEP, DIBP, DBP, BEEP, DNPP, DHP, DCP, DEHP, DNOP, Dinonyl phthalate, seven aliphatic hydrocarbons(n-Tridecane, n-Tetradecane, n-Pentadecan-e, n-Hexadecane, n-Heptadecane, n-Octadecane, n-Nonadecane, Isoquinoline, 2-Chloropyridine, 2-N-itrophenol, and Benzophenone. The twenty two compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Additionally, there were higher proportions of DEP than DMP in Spring at all sites, and the ratio varied from 1.4 to 4.4 times while the ratio of DEP to DMP ranged from 0.8 to 1.2 times in Summer. These results are consistent with the water quality of the Nakdong River [17]. As mentioned previously, DD is located at an estuary of the Nakdong River, so the seawater quality at DD can be affected by the water quality of the Nakdong River.…”
Section: Occurrence Tendency Of Pes In the Southeast Coast Region South Koreasupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, there were higher proportions of DEP than DMP in Spring at all sites, and the ratio varied from 1.4 to 4.4 times while the ratio of DEP to DMP ranged from 0.8 to 1.2 times in Summer. These results are consistent with the water quality of the Nakdong River [17]. As mentioned previously, DD is located at an estuary of the Nakdong River, so the seawater quality at DD can be affected by the water quality of the Nakdong River.…”
Section: Occurrence Tendency Of Pes In the Southeast Coast Region South Koreasupporting
confidence: 89%
“…As mentioned previously, DD is located at an estuary of the Nakdong River, so the seawater quality at DD can be affected by the water quality of the Nakdong River. DEP and DEHP were the most frequently detected PEs in the effluent of a wastewater treatment plant (WWTP) in the Nakdong River Basin [17]. It was also reported that the DEHP concentration range was wide and that the highest concentration was 12.293 µg/L due to the characteristic of the industrial complex occupying the Nakdong River, whereas the DMP detection rate was the lowest (47.4%) and the concentration was 0.954 µg/L [17].…”
Section: Occurrence Tendency Of Pes In the Southeast Coast Region South Koreamentioning
confidence: 98%
See 1 more Smart Citation